2007
DOI: 10.1007/s10573-007-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat of explosion of commercial and brisant high explosives

Abstract: Methods for determining the heat of explosion of high explosives (HEs) with ideal and nonideal processes of explosive decomposition are considered. It is shown that the heat of explosion is of significance for estimating the efficiency of commercial HEs and is used in the energetic characterization of the working capacity. The heat of explosion of brisant HEs is only part of the blast heat of explosion and is the heat content of gaseous detonation products during their isentropic expansion from the initial sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…This larger Q has been labeled Q max [4,42]. It is Q max that is related to sensitivity [38,[40][41][42][43]49].…”
Section: Properties Governing Detonation Velocity and Detonation Presmentioning
confidence: 99%
“…This larger Q has been labeled Q max [4,42]. It is Q max that is related to sensitivity [38,[40][41][42][43]49].…”
Section: Properties Governing Detonation Velocity and Detonation Presmentioning
confidence: 99%
“…What is more, high power emulsion explosives also can save the quantity of explosive charge or the number of blastholes. Consequently, high-power emulsion explosive research has received attention from researchers in the field of industrial explosives [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the four decomposition paths can be extended for non-ideal aluminized explosives with the general formula CHNOFClAl, and gives a more reliable detonation pressure [27] and velocity [28] as compared to the outputs of complex computer codes. Due to the importance of using AN in commercial explosives [15,16], the study on various detonation products and their interactions with Al, as well as partial decomposition of AN, shows that it is possible to improve the predictive power of recent studies [27,28] for a wide range of CHNOFClAl(AN) explosives. A study of the heats of detonation and available experimental data of detonation velocities, which were collected from the open literature, showed that the decomposition paths in previous studies [27,28,30,33,34] shows the appropriate decomposition paths in which the percent participation of Al and AN in these reactions depends on the oxygen content of the other ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, a non-ideal explosive has significantly different detonation properties to those predicted by well-known computer codes or empirical methods [11,12]. Aluminum (Al) and ammonium nitrate (AN) have wide applications in the explosives industry [15][16][17][18][19]. Explosives containing these compounds show non-ideal behaviour [11,12].…”
Section: Introductionmentioning
confidence: 99%